The Relationship Between The Male And Female Language Performance And The Level Of Anxiety Among Iranian EFL Students - Janfaza, Abusaied; Rezaei, Yousof; Soori, Afshin (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
This study tries to investigate the relationship between the male and female language performance and the level of anxiety among Iranian EFL students. The participants of the current study were 26 Iranian EFL students studying English in Islamic Azad University, Larestan, Iran who were selected in terms of the administering of an Oxford Placement Test. Then, the students were given The Foreign Language Classroom Anxiety Scale. Finally, they were given an English class test which consisted of 40 multiple-choice items. The researcher calculated the correlation between the Foreign Language Classroom Anxiety Scale and the performance of both Iranian male and female students on English Class test. The findings indicated that there was a negative correlation between the level of anxiety and the students’ performance on English Class Test scores. Moreover, Iranian male students were more anxious in learning English than female students.